Analisis Pengaruh Kepemimpinan, Disiplin dan Motivasi Kerja Terhadap Kinerja Karyawan CV. Berkah Jaya Utama - Nanang Suherman (Jurnal Syntax Transformation, 2022)
This study aims to describe the problems that exist in the CV. Berkah Jaya Utama, where the printing and stationery business sector development has become an opportunity for small companies for sub-sectoral work. Take advantage of opportunities in reaching consumers, creating competition between similar printing companies. This also makes every company innovate creative marketing strategies to sell the services offered to the target audience. CV. Berkah Jaya Utama is a printing company founded in 2008 and is engaged in printing and stationery. The obstacle that often occurs is when many printing orders must be completed on time. In this situation, leadership direction, company motivation, and good working environment between work fields at CV. Berkah Jaya Utama so that employee performance can be followed up as soon as possible so as not to cause disappointment from consumers